Narrative Review of Drug-Associated Nail Toxicities in Oncologic Patients - Emvalomati, Anastasia; Oflidou, Valentina; Papageorgiou, Chryssoula; Kemanetzi, Christina; Giannouli, Maria; Kalloniati, Evangelia; Efthymiadis, Konstantinos; Koukoutzeli, Chrysanthi; Timotheadou, Eleni; Trigoni, Anastasia; Patsatsi, Aikaterini; Lazaridou, Elizabeth; et al. (Dermatology Practical & Conceptual, 2023)
Introduction Nail toxicity represents one of the most common cutaneous adverse effects of both classic chemotherapeutic agents and new oncologic drugs, including targeted treatments and immunotherapy. Objectives We aimed to provide a comprehensive literature review of nail toxicities derived from conventional chemotherapeutic agents, targeted therapies (EGFR inhibitors, multikinase inhibitors, BRAF and MEK inhibitors) and immune checkpoint inhibitors (ICIs), including clinical presentation, implicated drugs and approaches for prevention and management. Methods Retrieved literature from PubMed registry database was reviewed to include all articles published up to May 2021 relevant to the clinical presentation, diagnosis, incidence, prevention, and treatment of oncologic treatment-induced nail toxicity. The was searched for relevant studies. Results A wide spectrum of nail toxicities is associated with both, conventional and newer anticancer agents. The frequency of nail involvement, especially with immunotherapy and new targeted agents remains unknown and patients with different cancer types receiving different regimens may develop the same nail disorder, whereas patients with the same type of cancer under the same chemotherapeutic treatment may develop different types of nail alterations. The underlying mechanisms of the varying individual susceptibility and the diverse nail responses to various anticancer treatments need further investigation. Conclusion Early recognition and treatment of nail toxicities can minimize their impact, allowing better adherence to conventional and newer oncologic treatments. Dermatologists, oncologists and other implicated physicians should be aware of these burdensome adverse effects in order to guide management and prevent impairment of patients’ quality of life.